Can a small nation be competitive in the global sporting arms race? The case of Denmark - Storm, R. K.; Nielsen, K.; Thomsen, F. (Managing Sport and Leisure, 2016)
In 2014, the Danish elite sport organisation, Team Danmark (TD), celebrated its 30th anniversary. TD was founded by the government in response to the country`s decline in international standings. This study examines how Denmark`s international performance has developed in the global sporting arms race since then. It analyses how a small nation can improve its international competitiveness despite stagnating funding and growing international competition. The paper argues that the establishment of TD in 1984 is a key factor behind Denmark`s success in elite sport. Measured in absolute terms, by a market share approach, and adjusted for differences in population, wealth, religion and relevant political factors, it is evident that Denmark is performing well and appears to be competitive. Denmark is now the leading nation in Scandinavia and is doing better than almost all other smaller countries in the Summer Olympic disciplines. By examining the development of Danish elite sport policies, the paper shows how the establishment of TD has created an elite sport structure that has helped Denmark to bounce back from its previous decline.